Systematics of Eriocaulaceae in Thailand - Prajaksood, Amornrat (Trinity College (Dublin, Ireland). Department of Botany, 2006)
This thesis aimed to provide a complete account of the family Eriocaulaceae for Thailand, to resolve the identity of unknown Thai taxa in the family and to investigate the relationship between Thai species using morphological, anatomical, and molecular approaches.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin